Ultrasound Contrast Agents Targeting and Processing Methods for Theranostics - Paradossi, Gaio.; Pellegretti, Paolo; Trucco, Andrea; SpringerLink (Online service) (Milano : Springer Milan, 2010)
Recent advancements in nano/micro materials and related characterization approaches allow the design of a new type of ultrasound contrast agents (UCAs) with enhanced multifunctional behaviour. This is chance is also supported by the recent achievements in modelling and signal processing. This book provides the state of art of the research activity of two successful European projects, TAMIRUT and SIGHT, addressing an integrated system, encompassing the contrast agent, the hardware equipment and the processing strategies, as a key tool for a combined diagnostic and therapeutic approaches (theranostics) in medical ultrasound.
Towards Ultrasound Molecular Imaging -- Use of Microbubbles as Ultrasound Contrast Agents for Molecular Imaging -- Design of Novel Polymer Shelled Ultrasound Contrast Agents: Towards an Ultrasound Triggered Drug Delivery -- Lipidic Microbubble Targeting of Surface Proteins Using an in Vitro System -- Protein Interactions with Microballoons: Consequences for Biocompatibility and Application as Contrast Agents -- Polymer Based Biointerfaces: A Case Study on Devices for Theranostics and Tissue Engineering -- Ultrasound Contrast Agent Microbubble Dynamics -- Characterization of Acoustic Properties of PVA-Shelled Ultrasound Contrast Agents -- Novel Characterization Techniques of Microballoons -- A Comparative Analysis of Contrast Enhanced Ultrasound Imaging Techniques -- Remote Measurement of the Ultrasound Contrast Agent Concentration -- Bubble Behavior Testing (BBT) System for Ultrasound Contrast Agent Characterization -- A New Flexible Ultrasound Scanner Suitable for Research Topics.
Keywords: Engineering; Medicine; Biochemistry; Radiology, Medical; Diagnosis, Ultrasonic; Biomedical engineering; Materials; Engineering; Biomedical Engineering; Molecular Medicine; Imaging / Radiology; Ultrasound; Medicinal Chemistry; Materials Science, general